Meneguhkan Karakteristik Pendidikan Islam dalam Arus Diskursus Kontemporer - Rustandi, Feri; Acep Ruskandar; Dienha Habibie; Adang Hambali; Hasan Basri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Islamic education today stands at the crossroads of rapid and complex global transformations, marked by modernization, digitalization, secularism, and the globalization of values. These changes pose significant challenges to the fundamental characteristics of Islamic education, particularly in preserving the core values of tawhid, adab (ethics), and morality. This study aims to reaffirm the essential identity of Islamic education in response to contemporary discourses and pressures. Using a qualitative approach through library research and Islamic educational philosophy, this study explores three main focuses: the challenges and threats to the identity of Islamic education, efforts to reinforce its core values through ethical, philosophical, and epistemological integration, and strategic innovations to ensure its adaptability and relevance. The findings reveal the need for a paradigm shift in Islamic education one that is both faithful to its spiritual foundations and responsive to the demands of the modern world. Islamic education must emerge as a dynamic and value-based system capable of shaping morally grounded, intellectually empowered, and globally competent generations.